Contemplating Mindfulness at Work: An Integrative Review. (January 2016) - Good, Darren J.; Lyddy, Christopher J.; Glomb, Theresa M.; Bono, Joyce E.; Brown, Kirk Warren; Duffy, Michelle K.; Baer, Ruth A.; Brewer, Judson A.; Lazar, Sara W.
Mindfulness research activity is surging within organizational science. Emerging evidence across multiple fields suggests that mindfulness is fundamentally connected to many aspects of workplace functioning, but this knowledge base has not been systematically integrated to date. This review coalesces the burgeoning body of mindfulness scholarship into a framework to guide mainstream management research investigating a broad range of constructs. The framework identifies how mindfulness influences attention, with downstream effects on functional domains of cognition, emotion, behavior, and physiology. Ultimately, these domains impact key workplace outcomes, including performance, relationships, and well-being. Consideration of the evidence on mindfulness at work stimulates important questions and challenges key assumptions within management science, generating an agenda for future research.